Wednesday

April 16, 2014

April 16, 2014

Posted by **jeana** on Sunday, July 3, 2011 at 11:15pm.

(a - b)2 = [a + (-b)]2

= a2 + 2a(-b) + (-b)2

= a2 – 2ab + b2

- math -
**Henry**, Tuesday, July 5, 2011 at 8:47pmHe is correct.

**Related Questions**

math - Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can ...

math 213 - Kahlil said that using the equation he can find a similar equation ...

math - Show that the formula for a line through two points (a1,b1) and (a2,b2) ...

Math - Draw a diagram to represent the identity (a + b)2 = a2 + 2ab + b2.

Maths - If cosec A – sin A=a3 , sec A – cos A =b3 , prove that a2 b2 (a2 + b2)=1...

algebra homework - f(x) and g(x) are monic quadratic polynomials that satisfy ...

chemistry - The initial state of a reaction is A2 +B2 –> 2AB. In the initial ...

chemistry - Vectors A B, and C satisfy the vector equation A+B=C and their ...

Chemistry - If a diagram describes an initial state of the reaction A2 + B2 --&...

Algebra - Why are these algebraic expressions used and explain the logical error...